2017
DOI: 10.1007/s00192-017-3455-8
|View full text |Cite
|
Sign up to set email alerts
|

Obesity: how much does it matter for female pelvic organ prolapse?

Abstract: In this observational study, we found a strong association between all tested measures of posterior compartment descent and BMI, both clinical and on imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 25 publications
2
10
0
5
Order By: Relevance
“…[1] There are, however, dissenting voices: Subak et al concluded that BMI had no impact on POP-Q data points [18], and Young et al showed that the association between BMI and prolapse was limited to posterior compartment prolapse. [19] The effect of weight reduction is controversial. While there seems to be a clear positive effect on symptoms of urinary incontinence, [18,20] this may not apply to prolapse symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] There are, however, dissenting voices: Subak et al concluded that BMI had no impact on POP-Q data points [18], and Young et al showed that the association between BMI and prolapse was limited to posterior compartment prolapse. [19] The effect of weight reduction is controversial. While there seems to be a clear positive effect on symptoms of urinary incontinence, [18,20] this may not apply to prolapse symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown a clear association between BMI and pelvic organ prolapse (POP) .Aa recent metaanalysis has found that overweight and obese women are more likely to have pelvic organ prolapse compared with women with body mass index in the normal range [1]. This is found to be true mainly for posterior compartment prolapse [2]. The associations between obesity and prolapse were found to be the strongest for objectively measured prolapse [1].…”
Section: Introductionmentioning
confidence: 99%
“…Overweight and obese women are more likely to suffer from pelvic organ prolapse (POP) in general [23]. Young et al [24] found a strong association between all measures of posterior compartment descent (both clinical and on imaging) and higher BMI. Whether a higher BMI is associated with worse functional outcome following gynaecological surgery for POP is a controversial.…”
Section: Preoperative Fi Postoperative Fimentioning
confidence: 99%
“…The more vaginal births women have, the more likely it is for them to experience a prolapse. Other things that press down on the pelvic organs and the pelvic floor muscles that can lead to prolapse are persistent coughing, such as a smoker's cough or asthma, heavy lifting, constipation, and straining induced in the effort to empty the bowel [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%